2012
DOI: 10.4103/0377-4929.101731
|View full text |Cite
|
Sign up to set email alerts
|

Crystal violet stain as a selective stain for the assessment of mitotic figures in oral epithelial dysplasia and oral squamous cell carcinoma

Abstract: Crystal violet stain can be considered as selective stain for mitotic figures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…The abnormal mitotic figures are due to an abnormal increase in the number of centrioles or to a lack of coordination between the chromosomal cycle and the division of centrioles. 27,28 The search for scientific publications related to the comparison of various types of mitotic figures seen in oral epithelial dysplasia and SCC with H&E or Crystal Violet stains could not reveal any substantial data and to the best of our knowledge our findings are the first of its kind. It is therefore proposed that since the type of mitotic figures found are directly related to the stage of progression of the pathology therefore, higher number of abnormal mitotic figures and metaphase cells with either stains could be due to the accumulation of these types of mitotic figures in SCC.…”
Section: Discussionmentioning
confidence: 73%
“…The abnormal mitotic figures are due to an abnormal increase in the number of centrioles or to a lack of coordination between the chromosomal cycle and the division of centrioles. 27,28 The search for scientific publications related to the comparison of various types of mitotic figures seen in oral epithelial dysplasia and SCC with H&E or Crystal Violet stains could not reveal any substantial data and to the best of our knowledge our findings are the first of its kind. It is therefore proposed that since the type of mitotic figures found are directly related to the stage of progression of the pathology therefore, higher number of abnormal mitotic figures and metaphase cells with either stains could be due to the accumulation of these types of mitotic figures in SCC.…”
Section: Discussionmentioning
confidence: 73%
“…A standardized, simple and quick stain with a set of welldefined criteria for the quantification of MFs will be effective and helpful. 2,3 In the present study, we aimed to identify a simple, costeffective and rapid technique for identification of MFs and also to evaluate its role in histological grading of oral epithelial dysplasia. It was observed that Feulgen stain provided superior staining of MFs facilitating its identification as compared to 1% crystal violet and H&E stains.…”
Section: Discussionmentioning
confidence: 99%
“…4 To date, light microscopy remains the gold standard for MF identification, among various other methods such as morphometry, immunohistochemistry, flow cytometry, DNA ploidy and nucleotide radiolabelling. 5 Malignant cells also exhibit considerable variations in terms of their morphology and dimensions, including pleomorphism, nuclear hyperchromatism and increased nuclear-to-cytoplasmic (N/C) ratios. 6 Various morphometric parameters including the shape and size of cells or cellular structures (i.e.…”
mentioning
confidence: 99%
“…10 Previous studies have utilised haematoxylin and eosin (H&E), Giemsa, crystal violet, toluidine blue and Feulgen stains to investigate chromatin patterns and identify MFs in brain, uterus and breast tissue. 2,5,11 However, few studies have employed Feulgen stains to stain paraffin-embedded sections of oral dysplasia and OSCC cells. 8,10 This study aimed to compare the number of MFs assessed quantitatively in normal mucosa and OSCC samples using Feulgen and 1% crystal violet stains.…”
mentioning
confidence: 99%
See 1 more Smart Citation